UHV – Deposited Amorphous Tantalum and Tantalum–Nickel Films. (1977) - Schäfer, Alfred; Menzel, Günther
Abstract : Tantalum produced by ultra-high vacuum vapour quenching has been identified on the basis of various forms of evidence as amorphous tantalum. Tantalum in this amorphous form has a resistivity of 230μ Ω cm and a temperature coefficient of resistivity (TCR) of –60 ppm/K. The films are stable below –90°C. At higher temperatures the amorphous structure suddenly turns into coarse-grainedα tantalum. Alloying with a mole fraction of 20% to 55% resulted in amorphous tantalum-nickel films with a temperature coefficient between –300 ppm/K and +500 ppm/K. The structure of the tantalum-nickel films, which are stable up to 300°C, was investigated by transmission electron microscopy. Deposition of the tantalum on substrates heated to temperatures between –80°C and +150°C resulted in β tantalum, which turned intoα tantalum between 160°C and 240°C. The appearance of positive and negative temperature coefficients in the amorphous films indicates that even in the amorphous state different conduction mechanisms may exist. According to the clean deposition conditions no influence of the residual gas on the film properties can be expected.